PHYSICOCHEMICAL AND HEAVY METAL ASSESSMENT OF SHALLOW HAND-DUG WELL WATERS WITHIN MAKURDI TOWN, BENUE STATE, NIGERIA - Iortile, Terhile M.; Abah, Rejoice E.; Stephen, Evelyn O.; Stephen, Evelyn O.; Tyolumun, Joseph T.; Unom, Wilfred I.; Gbande, Justine M.; Nosa, Mercy; Onaji, Ann; Okopi, Paul A.; Burbwa, Vihiior; Weor, Timothy T.; et al. (FUDMA Journal of Sciences, 2026)
Water is a ubiquitous chemical substance essential for all forms of life, and access to safe drinking water is critical for public health and well-being. Globally, about 80 % of illnesses are linked to contaminated water and poor sanitation, contributing significantly to mortality rates, particularly in Nigeria and other developing countries. This study assessed the physicochemical properties and heavy metal content of shallow hand-dug well water consumed in Makurdi, Benue State. A total of twenty-five (25) wells were randomly sampled, with five wells selected from each of five locations (Adeke, Gaadi, Kanshio, Wurukum and North Bank). The samples underwent physicochemical and heavy metal analyses to determine compliance with World Health Organization (WHO) and National Agency for Food and Drug Administration and Control (NAFDAC) standards for potable water. Results showed that most physicochemical parameters conformed to WHO (2017) and NAFDAC (2019) standards. However, turbidity exceeded the recommended limit of 5 NTU in Kanshio (6.65±0.45 NTU) and Wurukum (6.24±0.08 NTU). Lead and zinc concentrations were within acceptable limits, while cadmium levels were slightly elevated in Gaadi (0.107±0.005 mg/L), Kanshio (0.086±0.001 mg/L), and Adeke (0.12±0.001 mg/L). Nickel concentrations were also marginally above the permissible limit of 0.02 mg/L across all sampled locations. Overall, most parameters complied with WHO and NAFDAC guidelines, suggesting the water is generally safe for domestic use. However, proactive measures are necessary to control cadmium and nickel levels, as prolonged exposure may pose cumulative health risks.